Tocilizumab‐induced pancreatitis: case report and review of data from the FDA Adverse Event Reporting System. (27th September 2016) - Flaig, T.; Douros, A.; Bronder, E.; Klimpel, A.; Kreutz, R.; Garbe, E.
Summary: What is known and objective: Tocilizumab (TCZ) is a humanized monoclonal antibody acting against the IL‐6 receptor. It is a drug used in the treatment of rheumatoid arthritis and can be either given intravenously every 4 weeks or subcutaneously once a week. Known adverse events (AE) associated with TCZ include: infections of the upper respiratory tract, arterial hypertension, hypercholesterolaemia and hypertriglyceridaemia. Here, we present the first well‐documented case of TCZ‐induced acute pancreatitis (AP) and a systematic review of the literature including data from the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods: Patient data collection was performed within the Berlin Case–Control Surveillance Study. A literature search for TCZ‐induced AP was conducted. Analysis of the FAERS database concerning TCZ‐associated pancreatic AE from the period of 2009 until the first quarter of 2013 was conducted. Results and discussion: A 40‐year‐old man presented with a 2‐day history of progressive upper abdominal pain with elevated serum lipase and triglyceride levels. Biliary pancreatitis was ruled out by abdominal sonography and CT scan. Cessation of intravenously administered TCZ resulted in improvement of the patient's condition and a decline in elevated laboratory values, suggesting a probable relationship between TCZ intake and AP. Analysis of the FAERS database retrieved 52 cases of TCZ‐associated AP that accounted for 70% of all pancreatic AE in association with TCZ use. Further literature search detected three additional cases in which TCZ use was associated with AP. What is new and conclusion: Physicians should be aware of the probable association between TCZ use and AP. Targeted post‐authorization studies are needed to confirm and quantify the risk of TCZ‐induced AP.